A violência de alunos contra professores: a representação das escolas públicas de Goiânia-GO - Lôbo, Joice Duarte Batista (2012)
This dissertation has chosen as its objective the study of violence by students against teachers in state schools in the city of Goiania. Permeating the understanding of violence by students against teachers. The study aimed to conceptualize the terminology of violence in schools, contextualizing its nature, cause and consequence. The intention was also to identify the social mechanisms of school that contribute to the characterization of social practices, values and behaviors that indicate violence within the school unit. The study was also to meet the violent practices of students against teachers to contribute to building a database specific to the issue of violence in schools. For both the research paper talks about the factors that generate violence by students against teachers in public schools in Goiânia-GO. To account for this work was the study of literature about the violence, focusing on aspects related to the proposed objectives. The theoretical framework and methodology of this study is the theory of social representations, guiding the foundation of understanding representations of violence in schools. Data collection occurred through the empirical selection of eight public schools in the city of Goiania. For the data collection questionnaire was administered to 360 students and 40 teachers in these schools. The results from the literature and empirical research indicate that for adolescents to violence is linked to their life experiences, being a phenomenon present in everyday school, neighborhood, family and society. Violence at school and with teachers, manifested through physical and verbal aggression as a way of resolving interpersonal conflicts.